PENGARUH WABAH COVID-19 TERHADAP TINGKAT PENGANGGURAN TERBUKA PADA SEKTOR TERDAMPAK DI INDONESIA - Agustiana, Layli Eksak (Jurnal Ilmu Manajemen Terapan, 2020)
Covid-19 pandemic which took place since the beginning of the year has hit the economy, including in Indonesia. The business sectors, especially tourism and manufacturing are the most affected. The result is the termination of employment (layoffs) or laying off workers for a while. Based on data from the Ministry of Manpower and BPJS Employment, there are 2.8 million workers directly affected by Covid-19. They consist of 1.7 million formal workers laying off and 749.4 thousand laid off. In addition, there were 282 informal workers whose businesses were disrupted. While the Badan Perlindungan Pekerja Migran Indonesia (BP2MI) recorded that there were 100,094 Pekerja Migran Indonesia (PMI) from 83 countries returning to Indonesia in the last three months. CORE Indonesia estimates that the open unemployment rate in the second quarter of 2020 will reach 8.2% with a mild scenario. While other scenarios were 9.79% in the medium scenario and 11.47% were severe scenarios. The Indonesian Monetary Fund (IMF) also projects Indonesia's unemployment rate in 2020 to be 7.5%, increasing from 2019 which is only 5.3%.